Comparative Analysis of Dasatinib Effect between 2D and 3D Tumor Cell Cultures - Samantha Sabetta; Davide Vecchiotti; Letizia Clementi; Mauro Di Vito Nolfi; Francesca Zazzeroni; Adriano Angelucci (MDPI AG, 2023)
Three-dimensional cell culture methods are able to confer new predictive relevance to in vitro tumor models. In particular, the 3D multicellular tumor spheroids model is considered to better resemble tumor complexity associated with drug resistance compared to the 2D monolayer model. Recent advances in 3D printing techniques and suitable biomaterials have offered new promises in developing 3D tissue cultures at increased reproducibility and with high-throughput characteristics. In our study, we compared the sensitivity to dasatinib treatment in two different cancer cell lines, prostate cancer cells DU145 and glioblastoma cells U87, cultured in the 3D spheroids model and in the 3D bioprinting model. DU145 and U87 cells were able to proliferate in 3D alginate/gelatin bioprinted structures for two weeks, forming spheroid aggregates. The treatment with dasatinib demonstrated that bioprinted cells were considerably more resistant to drug toxicity than corresponding cells cultured in monolayer, in a way that was comparable to behavior observed in the 3D spheroids model. Recovery and analysis of cells from 3D bioprinted structures led us to hypothesize that dasatinib resistance was dependent on a scarce penetrance of the drug, a phenomenon commonly reported also in spheroids. In conclusion, the 3D bioprinted model utilizing alginate/gelatin hydrogel was demonstrated to be a suitable model in drug screening when spheroid growth is required, offering advantages in feasibility, reproducibility, and scalability compared to the classical 3D spheroids model.